Differential Cross Sections of 9Be(d,p0)10Be, 9Be(d,p1)10Be, 9Be(d,α0)7Li and 9Be(d,α1)7Li reactions - Tsavalas, P.; Lagoyannis, A.; Mergia, K.; Ntemou, E.; Lungu, C. P. (HNPS Advances in Nuclear Physics, 2019)
In the present work, the cross sections of the 9Be(d,p0)10Be, 9Be(d,p1)10Be,9Be(d,α0)7Li and 9Be(d,α1)7Li in the deuteron energy range Elab= 1 – 2.2 MeV with an energy step of 20 keV and at detection angles between 120o and 170o were measured, suitable for nuclear reaction analysis. A Si3N4film coated with a thin Be layer was used and the cross sections are determined relatively to the cross section of the natSi(d,d)natSi elastic scattering. Additionally, proton and oxygen beam measurements were carried out in order to determine the atomic areal density which is required to determine the cross sections.